Assessing the impact of a family empowerment program on asthma control and medication use in children with asthma: A randomized controlled trial. Issue 2 (9th January 2021) - Dardouri, Maha; Bouguila, Jihene; Sahli, Jihene; Ajmi, Thouraya; Mtiraoui, Ali; Zedini, Chekib; Mallouli, Manel
Abstract: Purpose: In pediatric asthma, family empowerment education has been beneficial for the quality of life, pulmonary function, and family functioning. Few studies addressed the impact of a family empowerment program on asthma symptom control, acute healthcare use (AHCU), and medication use in children with asthma. This study aimed to assess the effect of a family empowerment intervention on asthma symptom control, AHCU, inhaler technique, and controller adherence in children with asthma. Design and Methods: A single‐center study using a randomized controlled design was conducted in a university hospital in the center of Tunisia from May 2018 to September 2019. Eighty‐two families were randomly assigned to the intervention group ( n = 41) of 8 weeks of group training sessions, or to the control group ( n = 41) of usual care education. Thirty‐seven families in the intervention group and 39 families in the control group received allocated intervention at baseline. Thirty‐four families in each group completed the study at the 12‐month follow‐up. Results: At baseline, the intervention and control groups were statistically comparable ( p > .05). At follow‐up, there were significant differences between the intervention and the control group in asthma symptom control, χ 2 (1, N = 34) = 9.950, p = .002, and inhalation technique, χ 2 (1, N = 34) = 5.916, p = .01. For AHCU and adherence to asthma controller, there was no significant difference between groups, χ 2 (1, N = 34) = 3.219, p = .07, χ 2 (1, N = 34) = 0.541, p = .46, respectively. The difference within time in asthma symptom control and inhalation technique was significant ( p = 10 −3, p = .001; respectively). Practice Implications: This study demonstrated that a family empowerment program significantly improved asthma symptom control and inhaler technique in children with asthma aged 7–17 years. This intervention could be clinically useful and time‐saving for pediatric nurses.